2020
DOI: 10.1111/jvim.15826
|View full text |Cite
|
Sign up to set email alerts
|

Survival characteristics and prognostic importance of echocardiographic measurements of right heart size and function in dogs with pulmonary hypertension

Abstract: Background The clinical relevance of echocardiographic measurements of right heart size and function in dogs with pulmonary hypertension (PH) is unknown. Objective To determine if echocardiographic measurements of right heart size and right ventricular (RV) function are associated with survival times in dogs with PH. Animals Eighty‐two client‐owned dogs. Methods Retrospective study where data from medical records a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 50 publications
2
39
0
Order By: Relevance
“…Dogs with R-CHF in this study also showed RV dysfunction based on a decrease in RV-SL and RV-SrL and increased RV afterload based on TR velocity. Additionally, previous studies have reported that right heart dilatation is associated with the presence of R-CHF and shorter survival time ( 19 , 33 ). Therefore, our results suggest that the PVRecho2 and RVIDd index may provide additional information to determine the presence of R-CHF in dogs with MMVD.…”
Section: Discussionmentioning
confidence: 90%
“…Dogs with R-CHF in this study also showed RV dysfunction based on a decrease in RV-SL and RV-SrL and increased RV afterload based on TR velocity. Additionally, previous studies have reported that right heart dilatation is associated with the presence of R-CHF and shorter survival time ( 19 , 33 ). Therefore, our results suggest that the PVRecho2 and RVIDd index may provide additional information to determine the presence of R-CHF in dogs with MMVD.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, it can be an important index for RV assessment in diseases that lead to RV volume or pressure overload or systolic dysfunction, such as PH. 5 , 6 , 7 The reduction in RV systolic function in dogs with PH might result in consequences for treatment or life expectancy. Also in dogs with myxomatous mitral valve disease, the RV function indices might serve as additional prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…The RV plays an important role in many diseases affecting left heart, 1 , 2 right heart, 3 , 4 and causing pulmonary hypertension (PH). 5 , 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…It can induce various changes in the right heart, such as right ventricular (RV) hypertrophy, dilatation, and dysfunction, which might eventually lead to rightsided congestive heart failure (R-CHF) [12,46]. Recent study has reported that RV dilatation and systolic dysfunction were associated with worse outcomes in dogs with PH [45]. Additionally, several human studies have reported that RV diastolic dysfunction was also induced by PH through hypertrophy, fibrosis, and stiffening of RV cardiomyocytes [4-6, 27, 29, 41].…”
Section: Introductionmentioning
confidence: 99%